Another Black Witch Moth Record for Saskatchewan (Correction) - Carlson, Muriel (Blue Jay, 2023)
NOTE FROM THE EDITOR: This article was initially published in Blue Jay 80.4, regrettably with a number of errors. Below is the revised copy.